Sustainable fuel production from steam reforming of waste motor oil over olivine-supported Fe catalyst. (November 2021) - Phusuwan, Umponruch; Atong, Duangduen; Nisamaneenate, Jurarat; Sricharoenchaikul, Viboon
Abstract: Waste Motor Oil (WMO) has great potential to be utilized as a green fuel feedstock via thermochemical process as its high carbon content is suitable as alternative source during steam reforming reactions (SR). This process not only has potential for high syngas (CO and H2 ) production but also elimination of undesirable components, polyaromatic hydrocarbons (PAHs) and heavy metals in WMO. Here, evaluation of optimal conditions for WMO catalytic steam reforming in fixed-bed laboratory reactor to produce quality syngas was carried out. Influences of residence time (7–20 s), reaction temperature (700–900 °C), steam to carbon (S/C) ratio (1:2, 1:1, and 2:1), and Fe loadings (5% and 10%) on olivine support on carbon and hydrogen conversions were investigated. Results showed that the highest carbon and hydrogen conversions could be obtained after 10 s due to reactions achieving equilibrium. As for temperature, carbon and hydrogen conversions increased with temperature from mainly endothermic reactions which cause more hydrocarbon cracking. S/C volume ratio of 1:1 was preferable to obtain better carbon and hydrogen conversions due to superior heat distribution. Thus, the optimal conditions of WMO reforming were 10 s and S/C ratio of 1:1 at 800 °C which resulted in 94.68% and 79.34% carbon and hydrogen conversions, respectively, while gas product LHV was 4.44 MJ/m 3 . As for Fe loading on olivine, the best performance was acquired at 800 °C, residence time of 15 s, and S/C ratio of 1:1 with 10% Fe/olivine. Carbon and hydrogen conversions increased by 7.60% to 69.91% and by 13.70% to 69.31%, respectively, when compared to non-catalytic cases. This is because of higher cracking of heavy hydrocarbons from greater Fe active sites. Application of this work may lead to decrease in environmental impact from WMO disposal and make available the green fuel for sustainable power generations or as chemical intermediates in many industries.